(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Purpose: Most of the available academic literature points towards the absence of correlation or a slightly negative correlation between consumption of coffee and occurrence of breast cancer. However, the extent of risk differs when considering separate subgroups of, say, menopausal status, hormonal profile of the tumor or genetic mutations. The present review, based on the extensive literature search, will shed light on the possible effect of a ubiquitous beverage, coffee, on the risk of breast cancer development in the general population, in different female groups, and the consequences of coffee drinking after a breast cancer diagnosis and treatment. Results: This is consistent with the present review, which confirms that in the general population, coffee consumption is not significantly associated with the risk of breast cancer, and maybe in a weak protective effect at high levels of consumption. Moreover, coffee is associated inversely with the risk of breast cancer in postmenopausal women as well as women with BRCA1 mutation. Risk differences could be observed among people who are classified as being slow and fast caffeine metabolizers especially with regard to body weight. Post-diagnosis of breast cancer intake of coffee and subsequent post-surgery intake followed by tamoxifen use and/or radiotherapy has been associated with reduced recurrence events in the initial years following the diagnosis. The effects of coffee drinking seem to be less conclusive amongst some of the subpopulations namely premenopausal women, BRCA2 mutations, and individuals who were diagnosed with tumors with different hormonal patterns either being estrogen receptor/progesterone receptor positive or negative, thus requiring further research studies.